2021
DOI: 10.1292/jvms.21-0007
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit hemorrhagic disease virus type 2 epidemic in a rabbit colony in Japan

Abstract: Twenty-three of 42 European rabbits ( Oryctolagus cuniculus ), belonging to the same rabbit colony, died in March 2020 (55% mortality) in Chiba prefecture, Japan. The disease course was extremely acute without indicators of death or hemorrhage. Necropsy revealed liver swelling, discoloration, cloudiness and fragility, and pulmonary edema. Histologically, severe hepatocellular necrosis (mainly peripheral) and intra-glomerular capillary hyalin thrombi were observed. On molecular-biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The North American strains, including our 12 California sequences, are more similar to European than to Australian strains collected from 2016 onwards. In fact, RHDV2 originated in France in 2010 (Le Gall‐Reculé et al., 2011), and in 10 years has spread to five different continents (Ambagala, Ababio, et al., 2021; Fukui et al., 2021; Hu et al., 2021; Rouco et al., 2019). WGS and vp60 sequencing data from different parts of the world have confirmed that the circulating strains derive from European viruses (Mahar et al., 2018; O'Donnell et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The North American strains, including our 12 California sequences, are more similar to European than to Australian strains collected from 2016 onwards. In fact, RHDV2 originated in France in 2010 (Le Gall‐Reculé et al., 2011), and in 10 years has spread to five different continents (Ambagala, Ababio, et al., 2021; Fukui et al., 2021; Hu et al., 2021; Rouco et al., 2019). WGS and vp60 sequencing data from different parts of the world have confirmed that the circulating strains derive from European viruses (Mahar et al., 2018; O'Donnell et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this line, human intervention is considered a key factor in the rapid, worldwide spread of RHDV2 (Rouco et al, 2019). Reculé et al, 2011), and in 10 years has spread to five different continents (Ambagala, Ababio, et al, 2021;Fukui et al, 2021;Hu et al, 2021;Rouco et al, 2019). WGS and vp60 sequencing data from different parts of the world have confirmed that the circulating strains derive from European viruses (Mahar et al, 2018;O'Donnell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven RHD outbreaks were reported between 1998 and 2020 [9–14]. Thus far, genetic characterisation of Japanese strains has been performed using only a partial sequence of the major capsid gene, VP60 [10–13]. In this study, whole-genome sequencing of the Japanese RHDV strains and analysis of viral recombination events, followed by phylogenetic characterisation, were performed to completely understand the genetics of RHDV in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven RHD outbreaks were reported between 1998 and 2020 [9][10][11][12][13][14]. Thus far, genetic characterisation of Japanese strains has been performed using only a partial sequence of the major capsid gene, VP60 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%